Answer
1. \( (t + r)(x - y) \)
2. \( (b - a)(x + y) \)
3. \( (3a - x)(a + 2b) \)
4. \( (x -1)(x +1)(x + 3) \)
5. \( (2a +1)(1 - b) \)
6. \( (2x + y)(3x - a) \)
7. \( (a - b)(a + b)(4 + b) \)
8. \( -(x^3 -6)(x -1)(x +1) \)
9. \( (x -1)(x +1)(x - y)(x + y) \)
10. \( (x + y)(x^2 - xy + y^2 +1) \)
Solution
Let's factorize each expression step by step.
---
**1.** \( t x - t y + r x - r y \)
**Factorization:**
\[
t x - t y + r x - r y = t(x - y) + r(x - y) = (t + r)(x - y)
\]
---
**2.** \( b y - a x + b x - a y \)
**Factorization:**
\[
b y - a x + b x - a y = b y - a y + b x - a x = y(b - a) + x(b - a) = (b - a)(x + y)
\]
Alternatively, factoring out \(-1\) from \((b - a)\):
\[
= -(a - b)(x + y)
\]
---
**3.** \( 3 a^{2} - a x + 6 a b - 2 b x \)
**Factorization:**
\[
3a^2 - ax + 6ab - 2bx = 3a^2 + 6ab - ax - 2bx = 3a(a + 2b) - x(a + 2b) = (3a - x)(a + 2b)
\]
---
**4.** \( x^{3} + 3 x^{2} - x - 3 \)
**Factorization:**
\[
x^3 + 3x^2 - x - 3 = x^2(x + 3) -1(x + 3) = (x^2 -1)(x + 3) = (x -1)(x +1)(x + 3)
\]
---
**5.** \( 2 a - 1 - 2 a b + b \)
**Factorization:**
\[
2a - 1 - 2ab + b = 2a(1 - b) + 1(b -1) = (2a +1)(1 - b)
\]
Alternatively:
\[
= (2a + 1)(- (b -1)) = -(2a +1)(b -1)
\]
---
**6.** \( 6 x^{2} - a y - 2 a x + 3 x y \)
**Factorization:**
Rearrange terms:
\[
6x^2 - 2ax + 3xy - ay
\]
Factor by grouping:
\[
(6x^2 -2ax) + (3xy - ay) = 2x(3x - a) + y(3x - a) = (2x + y)(3x - a)
\]
---
**7.** \( 4 a^{2} - 4 b^{2} - b^{3} + a^{2} b \)
**Factorization:**
Rearrange and group:
\[
4a^2 + a^2b - 4b^2 - b^3 = a^2(4 + b) - b^2(4 + b) = (a^2 - b^2)(4 + b) = (a - b)(a + b)(4 + b)
\]
---
**8.** \( 6 x^{2} - x^{5} -6 +x^{3} \)
**Factorization:**
Rearrange:
\[
-x^5 + x^3 + 6x^2 -6 = -x^5 + x^3 +6x^2 -6
\]
Factor by grouping:
\[
(-x^5 + x^3) + (6x^2 -6) = -x^3(x^2 -1) +6(x^2 -1) = ( -x^3 +6)(x^2 -1)
\]
Factor further:
\[
(x^2 -1) = (x -1)(x +1)
\]
Thus:
\[
(-x^3 +6)(x -1)(x +1) \quad \text{or} \quad -(x^3 -6)(x -1)(x +1)
\]
---
**9.** \( x^{4} -x^{2} -x^{2} y^{2} + y^{2} \)
**Factorization:**
Rearrange:
\[
x^4 - x^2 y^2 -x^2 + y^2 = x^2(x^2 - y^2 -1) + y^2
\]
Notice that \(x^2 - y^2 = (x - y)(x + y)\), but let's try factoring by grouping:
\[
x^4 - x^2 y^2 - x^2 + y^2 = (x^4 - x^2 y^2) - (x^2 - y^2) =x^2(x^2 - y^2) -1(x^2 - y^2) = (x^2 -1)(x^2 - y^2) = (x -1)(x +1)(x - y)(x + y)
\]
---
**10.** \( x^{3} + y^{3} + x + y \)
**Factorization:**
Recall that \(x^3 + y^3 = (x + y)(x^2 -xy + y^2)\). Adding \(x + y\):
\[
x^3 + y^3 + x + y = (x + y)(x^2 -xy + y^2) + (x + y) = (x + y)(x^2 - xy + y^2 +1)
\]
Alternatively, factor out \((x+y)\):
\[
(x + y)(x^2 - xy + y^2 +1)
\]
Thus, the complete factorization is:
\[
(x + y)(x^2 - xy + y^2 +1)
\]
---
**Summary of All Factorizations:**
1. \((t + r)(x - y)\)
2. \((b - a)(x + y)\)
3. \((3a - x)(a + 2b)\)
4. \((x -1)(x +1)(x + 3)\)
5. \((2a +1)(1 - b)\)
6. \((2x + y)(3x - a)\)
7. \((a - b)(a + b)(4 + b)\)
8. \(-(x^3 -6)(x -1)(x +1)\)
9. \((x -1)(x +1)(x - y)(x + y)\)
10. \((x + y)(x^2 - xy + y^2 +1)\)
Reviewed and approved by the UpStudy tutoring team
Explain
Simplify this solution